The predictive power of luck: Luck and risk-taking in a repeated risky investment game - Stein Terje Holden; Sarah Tione; Samson Katengeza; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2022)
Can luck predict risk-taking behavior in games of chance? Economists have not widely studied this issue although overconfidence, optimism-, and pessimism bias have received substantial attention in recent years. In this study, we investigate how good and bad luck outcomes in a simple repeated risky investment game affect risk-taking behavior in the following rounds of the same game where the outcome (luck) in the game is determined by the throwing of a die after each round. The outcome of the previous round's die-throw is known when the subjects decide how risky their next choice in the game will be. A sample of 718 university students is used as subjects in the game in a recursive within-subject design. The results demonstrate a strong impact of luck on risk-taking behavior that lasts not only to the next round but also into another two follow-up rounds, with cumulative effects. A time delay of 1-2 months between Round 1 and Round 2 did not wipe out the luck effect and it was only slightly weaker than the luck effect from Round 2 to Rounds 3 and 4 that followed immediately after Round 2. Many recent studies have shown that risk preferences respond to recent shocks. This study indicates that random shocks such as luck in previous games (states of nature) influence risk-taking behavior. Our study suggests that the causal mechanism goes through subjective beliefs in luck based on past experiences that influence expectations and thereby risk-taking behavior.
Keywords: D8; H51; 330; Risky investment game; Luck; Illusion of control; Repeatedgame; Predictive power